THE EFFECT OF E-PROCUREMENT SYSTEM IMPLEMENTATION, COMPETENCE AND COMPENSATION ON EMPLOYEE PERFORMANCE OF GOODS/SERVICES PROCUREMENT - Nenden Maulida Yuliawati; Icih Icih; Asep Kurniawan (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
This research was conducted to analyze the magnitude of the effect of the partial and simultaneous implementation of the E-Procurement, Competence and Compensation System on the Goods / Services Procurement Employee Performance in Subang Regency. This research uses quantitative explanatory methods. The population and sample of the study are employees in the New / Service Procurement Unit in Subang Regency, so the total population is 31 people. Data collection methods used in this study are survey methods by distributing questionnaires. Where each respondent is given questions / statements as many as 32 items using a Likert scale. Data is processed using SPSS 22.0 version. Based on the results of data processing obtained results there is a positive and significant effect for the variable Application of E-Procurement, Competence and Compensation System partially and simultaneously to Employee Procurement of Goods / Services.